Implementasi Pendidikan Tasawuf Dalam Membentuk Toleransi Di Pondok Pesantren Sunan Kalijogo Jabung Malang - Rifqi, Akhmad (Impressive: Journal of Education, 2023)
Islamic boarding schools are educational institutions with a mission to eradicate ignorance and build character. The focus of this research is how the implementation process of sufism education in shaping tolerance in Sunan Kalijogo Jabung Malang boarding school. This research uses descriptive qualitative method with phenomenological approach. The implementation process of sufism education at the Sunan Kalijogo Jabung Malang boarding school in fostering and shaping the morals of the students through two stages, namely (1). Tasawuf Akhlaki (instilling the value of sufism in fostering character or morals) through several activities, including learning madrasah diniyah, learning the books of sufism, and tariqah. And (2). Tasawuf Amali (actualization of Sufism education), namely through spiritual activities (thariqah, tawajjuhan, khususiyah, and manjing suluk), and social activities (shaking hands culture, culture of using manners language, and community service. So that it will bring up several forms of tolerance attitudes towards oneself and others.